COMPETENCY-BASED CURRICULUM AND EMPLOYABILITY OF CURRICULUM AND PEDAGOGY STUDENTS, UNIVERSITY OF BAMENDA - Len, Kibinkiri Eric (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study examines the relationship between a Competency-Based Curriculum (CBC) and the employability skills of graduates from the Department of Curriculum and Pedagogy at the University of Bamenda, Cameroon, in response to increasing unemployment and underemployment among university graduates. Method: A correlational survey design was adopted, employing a structured questionnaire administered to 180 graduates selected through a mix of probability and non-probability sampling techniques. Descriptive and inferential statistical methods, including Spearman's Rho correlation test, were used to analyze the data. Results: The findings revealed a significant positive correlation between components of the CBC—such as learning challenges, content relevance, instructional delivery, and assessment methods—and the employability skills of graduates. The study further highlights that mentorship and educator support during program implementation play a crucial role in enhancing student competencies relevant to the labor market. Novelty: This research contributes to the limited empirical literature linking CBC to graduate employability in the Cameroonian context, offering evidence-based justification for educational reform. It underscores CBC as a strategic predictor of graduate success and advocates for its broader implementation in higher education institutions.